Influence of black shale composition on methane adsorption and gas content: Implications for gas storage in the Longmaxi black shales (2018)
The influence of shale composition on methane adsorption capability and gas content is investigated using 14 samples from Well YS8 in the southern Sichuan Basin, China. The results show that the Langmuir adsorption capacity of the Longmaxi shale is mainly a function of the total organic carbon (TOC) content. When TOC is ~1.1%, 50% CH4 is adsorbed onto the surface of the organic matter. The mineral content has limited control on the adsorption capacity of the Longmaxi shales. Organic matter is also a major control on gas content when TOC content is 1.0%. When TOC is 1.0%, gas content remains constant, indicating that gas preservation is more important than gas generation and rock adsorption capacity. Scatter plots of TOC versus gas content and, Langmuir adsorption capacity shows that when TOC is 2.0%, CH4 occurs both as free and absorbed gas, and CH4 occurs mainly as absorbed gas when TOC is 2.0%.